HOW TO TEACH WRITING SKILLS TO ESL AND EFL STUDENTS - Qodirova, Muhabbat (Журнал иностранных языков и лингвистики, 2021)
The current article is devoted to the particular theoretical views of the notion of writing skills as well as it focuses on ESL and EFL students. Moreover, it deals with the specialized characteristics which might be involved in most common used methods of teaching writing competence, particularly, on the examples of ESL and ELF students. Writing skills is a very important part of teaching and learning the target language. Aforementioned article shows how it is special to teach ESL and EFL students to write in their target languages. Moreover, there is informed about that Writing serves not only communicative purposes in professional activities but also in social ones. Meanwhile, as a communicative skill, sometimes we initiate the need to write. Other times, we respond to someone else’s initiation.